Equity in Higher education in Mexico: The need for a new concept and new policies - Silva Laya, Marisol (Education Policy Analysis Archives, 2012)
This article analyzes equity in Mexican higher education. It suggests a new conceptualization in educational equity based on a social justice definition that includes: effective access, compensation of inequalities, assuring permanence, and the achievement of meaningful results. Based on this framework, there is a warning that despite policies aimed at democratizing this public good, the education system still excludes thousands of young people from poor areas, and so many others are inadequately attended. The Mexican State has failed to ensure equal access for young people coming from disadvantaged areas and who have a different socio-economic and cultural background. In this light the meritocratic approach is questioned as a fair measure of distribution and advocates for the implementation of compensatory programs and affirmative action. In terms of school permanency, it is mentioned that the strategies and institutions addressed to the population that was excluded, do not always fulfill the basic quality requirements –infrastructure, teachers, libraries, technology, and must of all, relevant teaching practices. All this is deemed important in order to respond to the particular needs associated with youth’s low cultural capital in vulnerable areas. A way to overcome these problems is to generate equity policies that can guarantee a fair distribution of higher education that takes into account the disadvantages of large segments of young people so that their needs are addressed adequately.